Prediction of Bus Travel Time on Urban Routes without Designated Bus Stops in Makurdi Town, Benue State, Nigeria - Adeke, P. T.; Inalegwu, O. J.; Jirgba, K. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
The lack of information on bus travel time in Makurdi town to enable trip makers plan for journeys is seen as a challenge in recent times. This study developed a multiple linear regression model for predicting bus travel time along bus routes in Makurdi town. Specifically, the study assessed bus travel time on routes without designated bus stops, examined geometric features of bus routes, assessed bus dwell time and travel speeds in a heterogeneous traffic stream on routes in Makurdi town. It developed and validated a model for the bus travel time. Field survey focused on the major bus routes in Makurdi town which included; High Level roundabout to School of Remedial Studies junction (HL-SRS), High Level roundabout to Federal Medical Centre junction (HL–FMC), Wurukum roundabout to Coca Cola Complex (W-CCC) and Wurukum roundabout to Welfare Quarters junction (W–WQ). Independent parameters examined on the sites for model development included; bus route length, bus travel speed, average dwell time at random stops for pick-up and alighting of passengers, bus headway, the total number of cross and Tee intersections along the bus route, volume of motorcycles, private cars and trucks in the traffic stream, while the dependent variable was bus travel time. Based on the built model, 15 minutes approximately was established as the average bus travel time for all bus routes in Makurdi town assuming all other variables have zero magnitude. Goodness of fit test of the model yielded significant value for coefficient of determination (R2 = 0.952) and the use of Artificial Neural Network (ANN) method for validating the model also confirmed it accuracy at 93% approximately. It was therefore concluded that, bus travel time on major routes in Makurdi town could be accurately estimated using the built multiple linear regression model provided all essential input parameters of the model are used. The establishment of designated bus stops along bus routes within Makurdi town to minimise bus dwell frequency and for accurate estimation of bus travel time, as well as erection of travel information bill boards along bus routes stating average bus travel time to inform commuters that have high value of travel time were recommended.